Response to Issue-Based Social Movements in Nepal: Analyzing Dr. Govinda KC’s Satyagrah (Journal of Tikapur Multiple Campus, 2023)
Issue-based movements can generate strong responses in the social and political domain. Such movements, provided with an acknowledgement of impact and integrity, draw enough response from the civil society and the people in power. The main object of this paper is to know the social reality behind the issue based social movement of Dr. Govinda KC in Nepal. This is to answer a question why such reality exists and how the movement was addressed by the stakeholders. This qualitative analysis based on literature search, media monitoring and key informant interviews, finds that Dr. KC’s satyagraha had a larger public response and was taken as a commitment to the truth and social-justice issue in Nepal. However the government response, at some points, was seen from only one side of the power struggle. The government response to the peaceful demands that was highly supported by civil society was with unwanted delay, attempt of diffusion, and even with efforts for branding the civil society campaigners with political tools and using that attack as a way to detract from the popular demands challenging government’s democratic accountability.